Rebalancing Religious Policy and the Concept of Public Sphere: Indonesia Cases - Richard Sianturi, Petrus; Pardede, Josua Navirio; Dwi Riadi, Septian (Udayana Journal of Law and Culture; Vol 5 No 2 (2021)DO - 10.24843/UJLC.2021.v05.i02.p02, 2021)
As the largest Muslim country, Indonesia is on the way to balancing the order of its people, their religious practice, and how these two are influencing the public sphere. There is an existing regulation called Anti-Blasphemy Law which contains any rule to guarantee that religion and the public sphere do not contradict from one to another. Related to it, this research found that in this digital era with an advanced development on technology, some factors potentially create any form of manipulation on religion which comprises religion itself, social dynamic, and legal instrument. This form of manipulation has also triggered the advancement of the interdependency discourse on religion and the public sphere. In the context of Indonesia, by its characteristic, to separate religion and the public sphere will only create other problems among religious people. Using normative legal research, this paper aims to look at the relevance of the Anti-Blasphemy Law to the socio-structural conditions of Indonesian society. In this research, it is argued that religion and the public sphere (state) should be placed through a form of functional differentiation concept, and found that there is an interdependent relationship between religion and the public sphere, nevertheless, Anti-Blasphemy Law failed to create and maintain this relation. Hence, legal reform on the Anti-Blasphemy Law has become a necessity in ensuring a balanced and harmonious (state) religious life.